The subset composition of follicular T helpers and B lymphocytes in patients with ankylosing spondylitis depending on HLA-B27 status - P. A. Shesternya; A. A. Savchenko; I. V. Kudryavtsev; A. A. Masterova; A. G. Borisov (Сибирский научный медицинский журнал, 2024)
Immune relationships involved in a wide range of immunopathological conditions, including ankylosing spondylitis (AS), are formed due to the characteristics of the subset composition of follicular T helper cells (Tfh) and B lymphocytes. Expression of the HLA-B27 antigen can change the reactivity of cells of the immune system and, accordingly, their interaction and participation in the immunopathogenesis of AS. The aim of this study was to investigate the characteristics of the subset composition of Tfh and B cells in HLA-B27-positive and negative patients with AS. Material and methods. 66 patients (17 women and 49 men) aged 20–58 years with a diagnosis of AS were examined. Molecular genetic research on HLA-B27 expression was carried out using the quantitative PCR method with real-time detection. The subset composition of Tfh and B cells was studied using flow cytometry. Results. An increase in the amount of Tfh2 in the blood is observed in all patients with AS. The number of Tfh1 was reduced in HLA-B27-positive AS patients, but Tfh17 cell content was increased. Changes in the subset composition of B lymphocytes, which were found only in patients with an HLA-B27-positive form of the disease, manifest themselves primarily as an imbalance in the distribution of B cell memory. Only negative correlations of Tfh1 and Tfh17 content with “double-negative” B cell and plasmablast precursors percentage are detected in HLA-B27-negative AS patients. Tfh1 cell number correlate negatively with naïve and activated naïve B cell content in HLA-B27-positive disease, Tfh2 cell percentage – with memory B cell fraction number. CCR6+ Tfh and Tfh17 have positive regulatory effects on plasmablast precursors. Conclusions. The subset composition of Tfh characterizes the dominance in the immunopathogenesis of AS of the direction of the regulatory influence of follicular T helper cells on B lymphocytes regardless of the carriage of the HLA-B27 gene in AS patients. High levels of Tfh type 17 are also detected in HLA-B27-positive patients. The relationships between the subsets of Tfh and B cells in HLA-B27-negative AS patients characterize the presence of processes aimed at inhibiting B cells. The influence of Tfh1 is aimed at suppression of B-cell immunity in HLA-B27-positive AS while Tfh2 and Tfh17 stimulate B-cell mechanisms.